2012
DOI: 10.1371/journal.pone.0047769
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenetic Study of Drug-Metabolising Enzyme Polymorphisms on the Risk of Anti-Tuberculosis Drug-Induced Liver Injury: A Meta-Analysis

Abstract: BackgroundThree first-line antituberculosis drugs, isoniazid, rifampicin and pyrazinamide, may induce liver injury, especially isoniazid. This antituberculosis drug-induced liver injury (ATLI) ranges from a mild to severe form, and the associated mortality cases are not rare. In the past decade, many investigations have focused the association between drug-metabolising enzyme (DME) gene polymorphisms and risk for ATLI; however, these studies have yielded contradictory results.MethodsPubMed, EMBASE, ISI web of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
114
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(126 citation statements)
references
References 39 publications
(17 reference statements)
7
114
0
1
Order By: Relevance
“…Polymorphisms in CYP2E1 are present at higher frequencies in Asians than any other populations (Garte et al 2001), with a frequency of about 20-30% of the *5B allele (Khan et al 2009). According to the meta-analysis study by Cai (Cai et al 2012) the NAT2 slow genotypes, CYP2E1*1A and GSTM1 null have a modest effect on the genetic susceptibility to hepatotoxicity. Another study reported that the administration of the flavonoid quercetin could neutralize the hepatotoxicity mediator CYP2E1 (Tang et al, 2013).…”
Section: Association Among Clinical Factors Genotypes and Atd-inducementioning
confidence: 99%
See 1 more Smart Citation
“…Polymorphisms in CYP2E1 are present at higher frequencies in Asians than any other populations (Garte et al 2001), with a frequency of about 20-30% of the *5B allele (Khan et al 2009). According to the meta-analysis study by Cai (Cai et al 2012) the NAT2 slow genotypes, CYP2E1*1A and GSTM1 null have a modest effect on the genetic susceptibility to hepatotoxicity. Another study reported that the administration of the flavonoid quercetin could neutralize the hepatotoxicity mediator CYP2E1 (Tang et al, 2013).…”
Section: Association Among Clinical Factors Genotypes and Atd-inducementioning
confidence: 99%
“…Anti-tuberculosis drug-induced hepatitis (ATDinduced hepatitis) is an important clinical problem, being the most severe adverse effect during tuberculosis (TB) treatment (Tostmann et al 2008, Walker et al 2009, Cai et al 2012. Currently, the 6-month therapy consists in the combination of the drugs isoniazid (INH), rifampicin (RMP), pyrazinamide (PZA) and ethambutol (EMB) (Stine et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…NAT2 enzyme is responsible for acetylation step of isoniazid metabolism. 3,4,5,6,7,8,9 The activity of NAT2 (acetylator status) was strongly related to genetic variation on NAT2 gene. People with slow acetylator characteristic would have higher risk of hepatotoxic effect after tuberculosis treatment.…”
Section: Introductionsmentioning
confidence: 99%
“…Several studies had been studied about the relationship between acetylator status and risk of hepatotoxic; all of which showed a significant correlation. 3,5,6,9,10,11,12 Otherwise, the proportions of slow acetylator were varies in several studies. Thus indicated the different risk for hepatotoxic effect in different population.…”
Section: Introductionsmentioning
confidence: 99%
See 1 more Smart Citation